Pricing and hedging financial derivatives : a guide for practitioners - Marroni, Leonardo, 1980-; Perdomo, Irene, 1977- (Wiley finance series., 2014)
The only guide focusing entirely on practical approaches to pricing and hedging derivatives One valuable lesson of the financial crisis was that derivatives and risk practitioners don't really understand the products they're dealing with.